The Existence of the Indigenous People of Cek Bocek in Lawin Village, Sumbawa - Sumitro, Sumitro; Jumadi , Jumadi; Idrus , Idham Irwansyah; Kamaruddin, Syamsu Andi (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This research investigates the crucial role of indigenous peoples in contributing to global cultural diversity through the preservation of traditions and values passed down across generations. The study examines the existence of indigenous communities and the challenges they encounter in maintaining their identity, land, and culture in the modern era. A key focus is placed on documenting the rich cultural diversity of indigenous peoples, encompassing their languages, rituals, arts, and belief systems. Additionally, the research underscores the pivotal role indigenous peoples play in environmental conservation and sustainable management of natural resources. It also addresses the challenges posed by globalization, the lack of legal recognition, and resource conflicts, aiming to propose equitable and sustainable solutions. The study emphasizes the integration of traditional knowledge into inclusive development efforts, promoting a balanced relationship between humans and nature. The research employs a qualitative methodology, using observation, interviews, and documentation to provide comprehensive insights. The findings include two major areas: (1) Key Aspects of Indigenous Peoples' Existence, covering cultural diversity, relationships with nature, and social systems of balance; and (2) Challenges Facing Indigenous Peoples in the Modern Era, focusing on globalization and legal recognition.